Communicative Language Teaching: The Perceptions of English Teachers in Mempawah Hilir - Selvira Yanti, Gina (LPPM STBA Pontianak, 2017)
It is undeniable fact that English strengthens its role as international language day by day. In the response to this phenomenon, the Indonesian Ministry of Education has been trying to increase the quality of the education system since years ago; one of them is the changes of curriculum and its teaching approaches. Among many curricula that had been adapted in Indonesia, it is believed that communicative approach or communicative language teaching has mostly adapted in more than two changes of curricula. Therefore, the English teachers of Indonesia are assumed to be familiar with this teaching approach. The research had been done to 18 English teachers of junior high school level in Mempawah Hilir. Thus, the purpose of this paper is to review the results of an investigation about their perceptions in relation to their understanding on CLT principles, and their challenges in implementing CLT. Teachers’ perceptions itself is considered important because it reflects teachers classroom practices. By using cross-sectional descriptive survey research design, the data were derived from questionnaire and classroom observation checklist. It showed that, theoretically, the teachers had good understanding on the CLT principles. Unfortunately, in contrast, it did not reflect in their teaching practices. This phenomenon was caused mostly by some challenges identified from the questionnaire, for instance, big class size and student’s low English proficiency. In short, based on the results, it is hoped that this result can be one of references in making education/curriculum policy in the future.